Effects of Nodal inhibition on development of temnopleurid sea urchins. Issue 3 (28th May 2018) - Kasahara, Mami; Kobayashi, Chiaki; Sakaguchi, Chikara; Miyahara, Chisato; Yamanaka, Akira; Kitazawa, Chisato
Abstract : Adult rudiment formation in some temnopleurids begins with the formation of a cell mass that is pinched off the left ectoderm in early larval development. The cell mass forms the adult rudiment with the left coelomic pouch of the mesodermal region. However, details of the mechanisms to establish position of the cell mass are still unknown. We analyzed the inhibiting effect of Nodal, a factor for morphogenesis of the oral region and right side, for location of the cell mass, in four temnopleurids. Pulse inhibition, at least 5 min inhibition, during coelomic pouch formation allowed a cell mass to form on both sides, whereas treatments after that period did not. These results indicate that Nodal signaling controls the oral–aboral axis before gastrulation and then affects the position of the cell mass and adult rudiment up to coelomic pouch formation. They also indicate that the position of the adult rudiment under Nodal signaling pathways is conserved in temnopleurids, as adult rudiment formation is dependent on the cell mass.